Loss of CDX2 gene expression is associated with DNA repair proteins and is a crucial member of the Wnt signaling pathway in liver metastasis of colorectal cancer - Tóth, Csaba; Herpel, Esther; Schirmacher, Peter; Tiszlavicz, László (Oncology letters, 2018)
Caudal type homeobox 2 (CDX2) has been well-established as a diagnostic marker for colorectal cancer (CRC); however, less is known about its regulation, particularly its potential interactions with the DNA repair proteins, adenomatous polyposis coli (APC) and β-catenin, in a non-transcriptional manner. In the present study, the protein expression of CDX2 was analyzed, depending on the expression of the DNA repair proteins, mismatch repair (MMR), O6-methylguanine DNA methyltransferase (MGMT) and excision repair cross-complementing 1 (ERCC1), and its importance in Wnt signaling was also determined. A total of 101 liver metastases were punched into tissue microarray (TMA) blocks and serial sections were cut for immunohistochemistry. For each protein, an immunoreactive score was generated according to literature data and the scores were fitted to TMA. Subsequently, statistical analysis was performed to compare the levels of expression with each other and with clinical data. CDX2 loss of expression was observed in 38.5% of the CRC liver metastasis cases. A statistically significant association between CDX2 and each of the investigated MMRs was observed: MutL Homolog 1 (P<0.01), MutS protein Homolog (MSH) 2 (P<0.01), MSH6 (P<0.01), and postmeiotic segregation increased 2 (P=0.040). Furthermore, loss of MGMT and ERCC1 was also associated with CDX2 loss (P=0.039 and P<0.01, respectively). In addition, CDX2 and ERCC1 were inversely associated with metastatic tumor size (P=0.038 and P=0.027, respectively). Sustained CDX2 expression was associated with a higher expression of cytoplasmic/membranous β-catenin and with nuclear APC expression (P=0.042 and P<0.01, respectively). In conclusion, CDX2 loss of expression was not a rare event in liver metastasis of CRC and the results suggested that CDX2 may be involved in mechanisms resulting in the loss of DNA repair protein expression, and in turn methylation; however, its exact function in this context remains to be elucidated.
Gesehen am 26.04.2019